STRATEGI PENGEMBANGAN TENUN SATU KARYA PANDAI SIKEK: Analisis SWOT dan Bisnis Model Kanvas - Adil Fadhilah; Syukri Lukman; Syafrizal (Journal Publicuho, 2024)
The creative industry has been a long time that driven by the Indonesia government to improve people’s economic. A hand weaving businesses as part of creative industry are expected to maintain the quality and increase their productivity to gain competitive advantage in the coming market demands. This study is aimed on Tenun Satu Karya Pandai Sikek due to one of favorites weaving business in the province of West Sumatera.  By using business model canvas and SWOT analysis approaches on Tenun Satu Karya, it is expected to support competitive strategies on dynamic market demands. Results suggest that Tenun Satu Karya must focus on utilizing its strengths in the area of product quality and overcoming its weaknesses in the areas of partnerships, regeneration of the weaving craftsmen, and upgrading its marketing channels.